2017
DOI: 10.1186/s12913-017-2165-8
|View full text |Cite
|
Sign up to set email alerts
|

Where’s the evidence? a systematic review of economic analyses of residential aged care infrastructure

Abstract: BackgroundResidential care infrastructure, in terms of the characteristics of the organisation (such as proprietary status, size, and location) and the physical environment, have been found to directly influence resident outcomes. This review aimed to summarise the existing literature of economic evaluations of residential care infrastructure.MethodsA systematic review of English language articles using AgeLine, CINAHL, Econlit, Informit (databases in Health; Business and Law; Social Sciences), Medline, ProQue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…In Australia, the aged care sector is currently the subject of a Royal Commission that is placing an international spotlight on the shortfalls of the system and which is likely to highlight the need for significant policy reform to drive improvements in quality and efficiency when it issues its final recommendations at the end of this year [4]. A suite of recent systematic reviews have identified the paucity of economic evaluation evidence internationally, [5][6][7][8] yet economic evaluation forms a much needed component for policy reform to drive quality improvements and ensure that resources allocated across the aged care sector are targeted to services and programmes which maximise the quality of life (QoL) of older people [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, the aged care sector is currently the subject of a Royal Commission that is placing an international spotlight on the shortfalls of the system and which is likely to highlight the need for significant policy reform to drive improvements in quality and efficiency when it issues its final recommendations at the end of this year [4]. A suite of recent systematic reviews have identified the paucity of economic evaluation evidence internationally, [5][6][7][8] yet economic evaluation forms a much needed component for policy reform to drive quality improvements and ensure that resources allocated across the aged care sector are targeted to services and programmes which maximise the quality of life (QoL) of older people [6,7,9].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first study to examine the costs, resident quality of life, and numbers of hospitalisations associated with a clustered domestic model of care in Australia 19 , 20 . We found that a clustered domestic model of care is associated with better quality of life for residents, as well as fewer hospitalisations and emergency department presentations.…”
Section: Discussionmentioning
confidence: 76%
“…Despite ongoing discussions in the scientific literature about the economic and financial variables involved in the health and social care provision of the elderly, scarce data is available to support specific conclusions about cost-effectiveness, though results are promising for cost containment, disease prevention, and health of population [9, 2931]. A systematic review of respite for caregivers demonstrated that daycare is as costly as the usual care, but caregivers were satisfied and reported a positive effect on their mental or physical health [30].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of respite for caregivers demonstrated that daycare is as costly as the usual care, but caregivers were satisfied and reported a positive effect on their mental or physical health [30]. A novel approach has been suggested where the focus would be centred on the added value of care rather than cost saving [29], however, a more profound and accurate scientific analysis of cost-effectiveness, cost–benefit or cost-utility is needed [31].…”
Section: Discussionmentioning
confidence: 99%